16th Conference of the Lithuanian Sociological Association: Global challenges and future societies: Program and Abstracts, November 15–16, 2024, Vilnius University - Čiupailaitė-Višnevska, Dalia; Galdauskaitė, Dovilė; Poviliūnas, Arūnas; Norkus, Zenonas; Budginaitė-Mačkinė, Irma; Pivoriūtė, Milda (Vilnius University Proceedings, 2024)
-
Keywords: Sociology; conferences; symposiums; Lithuania; global challenges; future societies